SIRP Royan 1991. - Fleury, Jean-Christian (Royan : Ville de Royan, 1991)
Sohiez, Philippe ; Demarin, Ennio ; Prete, Nadia ; Assalit, Philippe ; Stawinski, Maciej ; Mouton, Jean-Claude ; van Leeuwen, Jan ; Xue-Hua Wu ; Nadeau, Didier ; Roosenboom, Kees ; Cassenx, Danielle ; Richard, Francis ; Broutschert, Hélène ; Silverio, Robert ; Montaut, Anne ; Pourcelot, Philippe-Liev ; Sawdon-Smith, Richard ; Colp, Norman B.
SIRP Royan 1991, Palais des Congres de Royan, 25 août au 15 septembre 1991
boek